2019
DOI: 10.3139/105.110398
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the Parameters of Induction Heat Treatment on the Mechanical Properties of 50CrMo4*

Abstract: Induction heat treatment facilities have a wide application range for heat treatment of cylindrically shaped materials in the steel processing industry due to their reduced process-time and high throughput. The adjustment of the heat treatment process usually aims at reaching a desired hardness. However, the question arises whether the full potential of the applied material is actually exploited. Therefore, this work systematically investigates the influence of the primary microstructure, austenitisation and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…UFH could strongly optimize industrial production processes in terms of time and consequently productivity [2][3][4][5]. Results very near to industrial applications were reported by Cola Jr. in AISI 8620 and in bainitic steels [6,7], but the most important limit appears to be related to UFH rates with respect to conventional steel-processing lines [8].…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…UFH could strongly optimize industrial production processes in terms of time and consequently productivity [2][3][4][5]. Results very near to industrial applications were reported by Cola Jr. in AISI 8620 and in bainitic steels [6,7], but the most important limit appears to be related to UFH rates with respect to conventional steel-processing lines [8].…”
Section: Introductionmentioning
confidence: 73%
“…UFH is a process based on induction heating (IH) that is widely used to heat-treat specific areas more rapidly, and at a lower cost and lower amount of energy consumption compared to conventional heat treatment methods [8,9]. The inductive heat treatment offers several advantages over conventional heat treatments using a furnace, such as short Metals 2022, 12, 1313 2 of 17 processing times, high flexibility, and localized annealing [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Promising results were reported concerning the application of the process to carbon steels [6,7]. Such results anyway also outlined the most important limitations of UFH process with respect to conventional steel-processing lines [8]. As a matter of fact, the increase in terms of heating rate strongly affects the phase transformation kinetics and as consequence steel mechanical properties: results reported in literature clearly show that an increase in terms of heating rate enhances the α/γ transformation temperature, with a refinement of the austenitic grain size [9][10][11][12].…”
Section: Introductionmentioning
confidence: 92%
“…Several studies demonstrated how microstructure and mechanical properties can be significantly modified by induction heat treatments applied to a wide range of iron-based materials and applications. Different research papers investigated the influence of operating parameters on the mechanical properties, with the focus on bulk materials [5][6][7], superficial aspects [8,9] and welded parts [10,11]. Guo et al [12] showed how the combination of the induction heat and surface peening treatments improved the yield strength without significantly impacting the ductility of pure iron.…”
Section: Introductionmentioning
confidence: 99%